Examining Patient Waiting Time with a Simulation Approach (Case Study: Emergency Department of Qaim Hospital, Mashhad) - Hasan Fatahi; Seyyed Mohammad Waziri; Mahyar Souri; Mohammad Hossein Askarian (Tehran University of Medical Sciences, 2023)
Background and purpose: The emergency department of a hospital is akin to its heart, where smooth operations can save many lives. This research aims to reduce patient waiting time in the emergency department using simulation techniques. Methods: This descriptive-analytical study was conducted cross-sectionally in 2019 at the Qaim Hospital in Mashhad. The study focused on accurately modeling the patient flow process in the emergency department using simulation techniques and Arena software. Key performance indicators such as patient waiting time, number of discharged patients (system output), length of stay, resource efficiency, and improvements in the emergency department were evaluated. Results: The simulation model's results indicated that the laboratory, specialist doctor examination, and pharmacy departments had the longest waiting times in this department, respectively. Conclusion: To reduce patient waiting times and improve conditions, the most effective and cost-efficient solution is to add a laboratory technician to the laboratory department during the [15-23] shift at Qaim Hospital in Mashhad, which is projected to decrease patient waiting times by 66 minutes.